Humor Rasulullah dalam Hadis: Etika Komunikasi Dakwah Humanis di Era Digital - Naria Giofandi (Arba: Jurnal Studi Keislaman, 2025)
Da’wah in the digital era faces serious challenges, including a crisis of empathy and a degradation of communication ethics, characterized by the emergence of rigid, offensive, and divisive narratives on various social media platforms. This situation demands a more humanistic and inclusive model of da’wah communication, one that can reach the audience emotionally without compromising its religious substance. This study aims to analyze the representation of the Prophet’s humor in the hadith as a model of da’wah communication ethics relevant to the digital context, while also providing an academic contribution by offering a communication framework based on prophetic values. The method used is a qualitative literature study approach, examining hadiths about the Prophet’s humor through the study of classical and contemporary commentators, and analyzing them using humanist communication theory. The analysis was conducted using interpretive-hermeneutic techniques to identify the principles of the Prophet’s humor and their relevance to contemporary da’wah practices. The results show that the Prophet’s humor is characterized by honesty, politeness, and a socio-educational function that is full of empathy and gentleness, so that it not only entertains but also educates and strengthens emotional bonds with the audience. The principles of the Prophet’s humor have proven to be an effective da’wah instrument because they can touch the psychological and spiritual aspects. In conclusion, the application of the Prophet’s humorous values in digital preaching can be effectively implemented through creative media, such as storytelling, Islamic memes, and educational videos, which are both communicative and fun, thereby presenting a friendly, inclusive, and transformative face of Islam to the global community.